University of ibadan students' coping strategies during the deployed emergency remote teaching (UI-ERT) (2022)
This study assessed University of Ibadan students' coping strategies during the deployed Emergency Remote Teaching (UI-ERT) as a response to the Covid_19 pandemic. It became necessary to salvage the crisis of physical distancing and learning losses as result of the virus. ERT abdication came with new innovations which students found difficult to cope until. One of the major effects of ERT is psychological cum emotional stress. The aim of the study was to assess students' coping strategies during the deployment of UI-ERT. Richard Lazarus Transactional Theory of Stress and Coping (TTSC) explained that stress ns a product of a transaction between person (including multiple systems, cognitive, physiological neurological) and his or her complex environment. The study adopted a mixed method research design. The population of the study comprised all undergraduate students of the institution. Purposive sampling technique was used to select 275 respondents while two self-designed instruments; SPUI-ERT (r=0.931) SCSDUI-ERT (r=0.939) were used in data collection. Data collected were analyzed using descriptive statistics of mean, frequency count, standard deviation, and percentage as well as PPMC. Thematic analysis was also carried on the interview conducted. The result indicated that the UI students had a negative perception of Emergency Remote Teaching (UI-ERT). It also revealed that UI students employed different coping strategies during the deployment of UI-ERT. The study therefore recommended thorough sensitization and pre-training programmes before the redeployment of the platform in case of any eventuality in the future.